2008
DOI: 10.1021/la7035949
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Effect of ZnO Nanoparticles Based on Bacteria

Abstract: Streptococcus agalactiae and Staphylococcus aureus are two pathogenetic agents of several infective diseases in humans. Biocidal effects and cellular internalization of ZnO nanoparticles (NPs) on two bacteria are reported, and ZnO NPs have a good bacteriostasis effect. ZnO NPs were synthesized in the EG aqueous system through the hydrolysis of ionic Zn2+ salts. Particle size and shape were controlled by the addition of the various surfactants. Bactericidal tests were performed in an ordinary broth medium on so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
277
1
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 571 publications
(302 citation statements)
references
References 29 publications
8
277
1
2
Order By: Relevance
“…Low-cost precursors ease synthetic procedure, short span of time scale along with biocompatible reactants allowed this reaction to be called as 'green'. Importantly, hexagonal structure of ZNP with (101) plane, the highest intense one, confirmed the growth along [0001] direction which might have impact on bacterial system (Huang et al 2008). Several studies have suggested, two possible mechanisms could be involved in the interaction between nanoparticles and bacteria-(a) the production of increased levels of ROS, mostly hydroxyl radicals and singlet oxygen (Ostrovsky et al 2009) and (b) deposition of the nanoparticles on the surface of bacteria or accumulation of nanoparticles either in the cytoplasm or in the periplasmic From our experimental results, we speculated that ZNP is first bound with hydrophilic counterpart of LPS resulting in some sort of deformation within OM.…”
Section: Discussionmentioning
confidence: 67%
“…Low-cost precursors ease synthetic procedure, short span of time scale along with biocompatible reactants allowed this reaction to be called as 'green'. Importantly, hexagonal structure of ZNP with (101) plane, the highest intense one, confirmed the growth along [0001] direction which might have impact on bacterial system (Huang et al 2008). Several studies have suggested, two possible mechanisms could be involved in the interaction between nanoparticles and bacteria-(a) the production of increased levels of ROS, mostly hydroxyl radicals and singlet oxygen (Ostrovsky et al 2009) and (b) deposition of the nanoparticles on the surface of bacteria or accumulation of nanoparticles either in the cytoplasm or in the periplasmic From our experimental results, we speculated that ZNP is first bound with hydrophilic counterpart of LPS resulting in some sort of deformation within OM.…”
Section: Discussionmentioning
confidence: 67%
“…The unique physico-chemical properties of ZnO NPs have made them one of the most commercialized nanomaterials used in a variety of applications such as sunscreen products and textiles (Stoimenov et al 2002;Huang et al 2008, Jones et al 2008Akhavan et al 2009). ZnO NPs show activity as antibacterial materials against both Gram-positive and Gram-negative bacteria, including spores.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, antibacterial nanoparticles influence several structures and biological pathways found in a wide range of pathogenic bacteria. This makes it harder for bacteria to develop resistance against nanoparticles (Nel et al 2009;Huang et al 2008;Pal et al 2007). …”
Section: Introductionmentioning
confidence: 99%